2010
DOI: 10.1074/jbc.m110.112094
|View full text |Cite
|
Sign up to set email alerts
|

Isoproterenol and cAMP Block ERK Phosphorylation and Enhance [Ca2+] Increases and Oxygen Consumption by Muscarinic Receptor Stimulation in Rat Parotid and Submandibular Acinar Cells

Abstract: Salivary glands are innervated by sympathetic and parasympathetic neurons, which release neurotransmitters that promote fluid secretion and exocytosis when they bind to muscarinic and ␤-adrenergic receptors, respectively. Signaling pathways downstream of these receptors are mainly distinct, but there is cross-talk that affects receptor-dependent events. Here we report that the ␤-adrenergic ligand isoproterenol blocks increases in extracellular signal-related kinase (ERK) phosphorylation, a protein kinase C-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 54 publications
(63 reference statements)
9
28
0
1
Order By: Relevance
“…In addition, VIP, VPAC1, and VPAC2 agonists failed to induce [Ca 2+ ] i responses in neurons. Some studies have shown that the β-adrenergic receptor agonist isoproterenol failed to induce [Ca 2+ ] i responses in rat parotid and lacrimal gland acinar cells (18,40,47). However, isoproterenol as well as forskolin promoted Ca 2+ release from intracellular stores by stimulating muscarinic and α-adrenergic receptors in rodent parotid acinar cells, which involved PKA-dependent phosphorylation of IP 3 R (3,9,44 ] i responses by U73122, thapsigargin, xestospongin C, and 2-APB in neurons indicated that these are primarily IP 3 -dependent.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, VIP, VPAC1, and VPAC2 agonists failed to induce [Ca 2+ ] i responses in neurons. Some studies have shown that the β-adrenergic receptor agonist isoproterenol failed to induce [Ca 2+ ] i responses in rat parotid and lacrimal gland acinar cells (18,40,47). However, isoproterenol as well as forskolin promoted Ca 2+ release from intracellular stores by stimulating muscarinic and α-adrenergic receptors in rodent parotid acinar cells, which involved PKA-dependent phosphorylation of IP 3 R (3,9,44 ] i responses by U73122, thapsigargin, xestospongin C, and 2-APB in neurons indicated that these are primarily IP 3 -dependent.…”
Section: Discussionmentioning
confidence: 99%
“…L'isoprotérénol, un agoniste des récepteurs -adrénergiques, inhibe la phosphorylation de la protéine ERK1/2 en aval de l'activation du récepteur P2X 7 [31]. En revanche, au niveau des glandes sous-maxillaires, des résultats divergents ont été obtenus.…”
Section: Les Voies De Signalisation Couplées Aux Récepteurs P2x Des Gunclassified
“…However, mitogenic signaling pathways such as those involving PKC, ERK, and Akt, as well as their M3R-mediated downstream events, are still poorly understood in the context of salivary gland cells. Only recently has a muscarinic receptor agonist, namely, carbachol (CCh), been reported to stimulate in vitro ERK phosphorylation in human immortalized salivary gland cells or rat submandibular acinar cells (Soltoff and Hedden, 2010). Because SjS is a chronic degenerative disease characterized by the gradual progression of cell apoptosis and resulting tissue destruction, it is plausible that mitogenic signaling, which can down-regulate apoptosis induced through the caspase pathway (Steelman et al, 2008), may play a role in sustaining the configuration and functions of affected glands.…”
Section: Introductionmentioning
confidence: 99%